Understanding Drug Abusers with HIV/AIDS through Qualitative Research - Andri, Anindya Jati; Poerwandar, Elizabeth Kristi; Dintari, Dunu Rahma (UI Scholars Hub, 2013)
This study analyzise the background of people’s situation on drugs dependency, their attitudes emerge after infected by HIV/AIDS, and ways to give self-meaning to themselves and their surroundings including actions to deal with their life problems. Style explanatory theory from Peterson & Seligman (1987) which is based on internal external dimension, stability-unstability/transient dan global-specific dimentions was used. This study was a in qualitative research with case study method. The objective is to explore the understanding of drug users with HIV/AIDS. The outcome from this research shows that most of the subjects were using external, stabilized and global patterns from explanatory theory in order to understand their dependecies on drugs and how hard for them to release from it ev enthough they knew that is harmful. The drug users who were infected by HIV/AIDS were hard, to understand their situations. This was caused by many factors such as social support, their physical and psychological conditions, public stigma that limit ways to facing their life. The constraints in this research were that all subjects were from one rehabilitation centre. Whereas, other understanding can be different in other rehabilitation centres which is women partic ipant, or people who were not under any rehabilitation program. Furthermore, the researcher found that a sense of responsibility to oneself can be a moral support for any subject to understand his/her needs and conditions.